The Use of Breast Cancer Survivor Patients as Part of Patient-Centred Education in the Training of Breast Cancer Care Nurses - E., Jalal; M., Nabishah; N.I., Safiah,; I., Fuad; K., Haslinda; A.R., Najibah, (IIUM Medical Journal Malaysia, 2021)
INTRODUCTION: Breast cancer is the most common cancer worldwide. Patients diagnosed with breast cancer face many psychological and social distress that might affect their quality of life and indirectly might affect the disease outcome. Patient-centred education has been found to have a positive influence on the quality of management and anxiety reduction. A one-day workshop involving breast cancer survivor patients was designed as a preliminary step to improve the quality of care provided by oncology nurses in University Kebangsaan Malaysia Medical Centre (UKMMC). The objectives of the workshop were to train the nurses in providing patient-centred education using breast cancer survivor patients and to implement the breast cancer Malaysian Clinical Practice Guidelines (CPG) recommendation. MATERIALS AND METHODS: One-day workshop was designed to meet specific learning outcomes. The patient education program was introduced with special emphasis on a patientcentred approach through the involvement of breast cancer survivor patients. Twenty-one staff nurses and two breast cancer survivor patients have participated in this workshop. The workshop was conducted by a breast cancer surgeon, oncologist, dietitian, family physician, and medical educators. RESULT: Overall, all participants found the workshop was very useful, particularly with the involvement of breast cancer survivor patients. Sixty – two percent of the participants agreed that the objectives of the workshop were met and 76 % of them found the workshop relevant to their work. CONCLUSION: The involvement of breast cancer survivor patients in this workshop was a valuable learning experience that enhanced the patient-centred approach in medical education.